Large Eddy Simulation in Duct Flow - Jalil, Jalal M.; Abbas, Ihab Omar (Al-Khwarizmi Engineering Journal, 2017)
In this paper, the problem of developing turbulent flow in rectangular duct is investigated by obtaining numerical results of the velocity profiles in duct by using large eddy simulation model in two dimensions with different Reynolds numbers, filter equations and mesh sizes. Reynolds numbers range from (11,000) to (110,000) for velocities (1 m/sec) to (50 m/sec) with (56×56), (76×76) and (96×96) mesh sizes with different filter equations. The numerical results of the large eddy simulation model are compared with k-ε model and analytic velocity distribution and validated with experimental data of other researcher. The large eddy simulation model has a good agreement with experimental data for high Reynolds number with the first, second and third mesh sizes and the agreement increase near the wall of the duct. The percentage error for the large eddy simulation model with experimental data of the (56×56) mesh size is less than 18 % and for the (76×76) mesh size is also less than 17% and for the (96×96) mesh size is less than 16 %. The large eddy simulation model show high stability and do not need extra differential equation like the k-ε model and a great saving in time and computer memory was achieved.